Employment protection: tough to scrap or tough to get? - Björn Brügemann (Institute for the Study of Labor (IZA), 2006)
Differences in employment protection across countries appear to be quite persistent over time. One mechanism that could explain this persistence is the so called constituency effect: high employment protection creates a mass of workers in favor of maintaining high protection because deregulation would mean that they would lose their jobs. To the extent that this mechanism is at work, employment protection would appear to be a policy that is difficult to deregulate once it has been introduced. In this paper I consider an alternative mechanism generating persistence that makes employment protection a policy that is difficult to introduce. If a legislative process is initiated to introduce employment protection, it is reasonable to assume that firms have an opportunity to lay off workers before employment protection becomes effective. Firms would have an incentive to do so in order to avoid the cost associated with stringent employment protection in the future. Anticipating this, workers whose situation is already precarious may not find it in their best interest to support the legislative process to introduce employment protection in the first place. The main result of the paper is that the ability of firms to adjust employment before an increase in employment protection becomes effective may give rise to situations in which both low and high employment protection are stationary political outcomes
Keywords: 330; Kündigungsschutz; Kündigung; Zeit; Schätzung; Großbritannien